Relationship of the Characteristics of Sediments and Organic Materials Sediment with the Abundance of Kerang Darah (Anadara granosa) in Tanjung Balai Asahan Waters, North Sumatra Province - Simanjuntak, Naomi; Rifardi, Rifardi; Tanjung, Afrizal (Faculty of Fisheries and Marine, Universitas Riau, 2020)
This research was conducted in March-April 2019 in the waters of Tanjung Balai Asahan, North Sumatra Province. Aim to determine the particle size of sediments, determine the abundance and distribution patterns of kerang darah (A. granosa), and analyze the effect of particle size of sediments and organic matter on the abundance of kerang darah (A. granosa). Sediment and kerang darah (A. granosa) samples were taken using a grab sampler from 4 stations, each station consists of 5 sampling points. The results showed that the environmental conditions of Tanjung Balai Asahan waters were still able to support the life of kerang darah (A. granosa). The type of sediment in these waters is dominated by sandy mud. The average diameter of sediments (Mz) 3-7.7 Ø with classification as very fine sand-very fine silt. The highest average content of organic sediment is found at station 2 (13.70%) which is located around the mangrove forest which is included in the classification of medium organic matter. The highest average value of kerang darah (A. granosa) abundance is at station 4 (54 ind/m2), with a clustered distribution pattern at all stations. The relationship between sediment characteristics and abundance of kerang darah (A. granosa) in Tanjung Balai Asahan waters is classified as a strong relationship with a determination coefficient (R2) of 0.529, this means that the size of sediment particles 52.9% affects the abundance of kerang darah (A. granosa) throughout the station while the remaining 41.7% are influenced by other factors not examined. The relationship of the content of organic matter with the abundance of kerang darah (A. granosa) is classified as a weak relationship, with a coefficient of determination (R2) of 0.004, meaning that the content of 0.4% sediment affects the abundance of kerang darah (A. granosa) throughout the temporary station 99.6% is influenced by other factors not examine.